Stunting and selection effects of famine: a case study of the great Chinese famine - Tue Gørgens; Xin Meng; Rhema Vaithianathan (Institute for the Study of Labor (IZA), 2007)
The Great Chinese Famine of 1959-1961 is puzzling, since despite the high death rates, there is no discernable diminution in height amongst the majority of cohorts who were exposed to the famine in crucial growth years. An explanation is that shorter children experienced greater mortality and that this selection offset stunting. We disentangle stunting and selection effects of the Chinese famine, using the height of the children of the famine cohort. We find significant stunting of about 2cm for rural females and slightly less for rural males who experienced the famine in the first five years of life. Our results suggest that mortality bias implies that raw height is not always a good measure of economic conditions during childhood
urn:nbn:de:101:1-20080425530
Keywords: 330; Hungersnot; Unterernährung; Gesundheit; China